Effects of waterborne antidepressants on non-target animals living in the aquatic environment: A review - Sehonova, Pavla; Svobodova, Zdenka; Dolezelova, Petra; Vosmerova, Petra; Faggio, Caterina (The Science of the total environment, 2018)
After application, antidepressants, like other pharmaceuticals, are excreted from human body in their native form or as metabolites and enter the aquatic environment via different pathways. As concentrations of antidepressant residues in water continue to increase, their effects on non-target animals are being discussed. The aim of this study is to summarize current knowledge about the effects of wateborne antidepressants on non-target animals living in surface waters - invertebrates, fish and amphibians. Selective serotonin reuptake inhibitors such as fluoxetine, sertraline, and citalopram have been found to effect behavior, reproduction, and development in both invertebrates and vertebrates. Venlafaxine, belonging to the group of selective serotonin-noradrenalin reuptake inhibitors, not only affected behavior but also showed the potential to reduce survival in fish. Tricylic antidepressants are known to have various side-effects when consumed by humans. Moreover, in fish, exposure resulted in a significant increase in mortality, developmental retardation, morphological anomalies, and pathological changes in brain, heart, and cranial and caudal kidney. In addition, changes in antioxidant enzyme activity as well as increased lipid peroxidation were observed, even at the lowest tested concentrations. According to current knowledge, antidepressants occuring in surface water are able to affect the behavior, reproduction, development, and survival of aquatic invertebrates and vertebrates.
Keywords: Animals; Citalopram; Antidepressive Agents; Selective Serotonin Reuptake Inhibitors; chemické látky znečišťující vodu; fluoxetin; Invertebrates; Amphibians; Water Pollutants, Chemical; Fluoxetine; Fishes; Sertraline; ryby; Aquatic Organisms; Fish; selektivní inhibitory zpětného vychytávání serotoninu; vodní organismy; zvířata; antidepresiva; Serotonin Uptake Inhibitors; sertralin